Distortionary taxation and the free-rider problem - Felix Bierbrauer (Max Planck Institute for Research on Collective Goods, 2006)
This paper derives a version of the Samuelson rule, which takes not only the marginal costs of public funds into account but also the desirability of preference revelation. Under a linear income tax more able individuals suffer from a larger utility loss if taxes are raised to cover the cost of public good provision. This implies that these individuals are tempted to understate their valuation of the public good. Likewise, less productive individuals are inclined to exaggerate their valuation. These incentive concerns require the use of excessive taxes. They ensure a truthful revelation of preferences for the public good. Under an optimal utilitarian tax constitution, individuals are not granted influence on public good provision if the taxes needed to induce informative behavior are prohibitively high.
Keywords: D71; D82; H21; H41; 330; Public Good Provision; Revelation of Preferences; Distortionary Taxation; Two-dimensional Heterogeneity